A MODEL EUROPEAN? HERMANN HESSE'S INFLUENCE ON THE SUHRKAMP VERLAG. (January 2015) - Cornils, Ingo
ABSTRACT Hermann Hesse's pivotal role in helping to set up one of Germany's most renowned publishing houses, the Suhrkamp Verlag, has long been recognised. However, little attention has been given to the programmatic and philosophical influence he had on Peter Suhrkamp and his successor Siegfried Unseld. This article analyses Hesse's lasting impact on his publishers' views, especially their commitment to European and World literature. It charts the development of Hesse's thinking on Europe, explores Hesse's relationship with Peter Suhrkamp and Siegfried Unseld, and demonstrates how Hermann Hesse's books, political writings, correspondence and more than three thousand book reviews contributed to the 'Suhrkamp Culture'.